PENERAPAN METODE ANALITICAL HIERARCHY PROCESS DALAM PENENTUAN WARGA PENERIMA PROGRAM KELUARGA HARAPAN (PKH) (Studi Kasus : Kantor Lurah Tegal Sari Mandala II) - Lubis, Paulus; Nadeak, Berto; Hondro, Rivalri Kristianto (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2017)
There is a term citizens of citizens and citizens. People are more a political concept. The people show to those who are under one government and the government. The terms of the last citizen or people is opposed by the ruler. So the residents of the Family Hope Program (PKH) are those surveyed based on BPS and PKC or PKH quotas also determined by the Government. One of the most important citizens in PKH recipients. Of course the choice of citizens should be done as possible. Based on the problem, the AHP method used in this research is for the determination of the citizens by considering the aspects of the determination that has been determined by the Partnership. The determining aspects that are the basis of the determination by the Kelangkahan in the determination of the residents is the Introduction Place, Information Household and Social Economic Description. By using AHP method is expected to assist the leadership of Tegal Sari Mandala II Lurah Office to conduct the process of determining the residents so that more quickly and effectively. Being a reference to research related to Governmen Keywords: Decision Support System, AHP, Program Keluarga Harapan (PHP)